Standardisation of Techniques for Production and Enrichment of vermiwash - Thankamony K (Department of Soil Science and Agricultural chemistry, College of Horticulture, 2005)
The study on the ‘Standardization of Techniques for Production and Enrichment of Vermiwash’ was conducted at College of Horticulture, Vellanikkara, during the year 2003-2005 with the objective to standardize the substrate controlled environment for worm multiplication, to identify the enrichment techniques of vermiwash and to evaluate the efficiency of enriched vermiwash on crop and soil.